The Impact of Hedonic Shopping Motivation, Discounts, and Urge to Buy Impulsively on Impulse Buying: S-O-R Perspective - I Gusti Ayu Imbayani; Agus Wahyudi Salasa Gama (AIBPM Publisher, 2024)
Online transactions make things easier for both buyers and sellers. Impulse buying behavior can occur because of easy access to the goods one likes at the right price. Impulse buying can occur due to discounts given by sellers or hedonic buying motivation that grows within the buyer. The temptation to make rash purchases can often lead to more impulsive purchases. This research focuses on the relationship between discounts and hedonistic purchasing motivation in relation to impulsive purchasing and the function of the impulse to buy as a mediator in these connections. The sample for this research was 105 consumers who purchased goods using Shop Tokopedia. PLS-SEM is used in this study for data analysis. The study's findings demonstrate that discounts have no direct impact on impulsive purchases. The desire to make impulsive purchases is significantly and favorably impacted by discounts. Impulsive buying and the desire to make an impulsive purchase are strongly impacted by hedonic buying motivation. The association between discounts and hedonic shopping motivation and impulse buying is mediated by the desire to make an impulsive purchase. The research implications show that stimulus in the form of discounts or hedonic buying motivation will influence consumers' emotions which will have an impact on their purchasing behavior.